2006
DOI: 10.1111/j.1745-3984.2006.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of IRT Fixed Parameter Calibration Methods

Abstract: This article provides technical descriptions of five fixed parameter calibration (FPC) methods, which were based on marginal maximum likelihood estimation via the EM algorithm, and evaluates them through simulation. The five FPC methods described are distinguished from each other by how many times they update the prior ability distribution and by how many EM cycles they use. Specifically, the five FPC methods included no prior weights updating and one EM cycle (NWU‐OEM) or multiple EM cycles (NWU‐MEM), one pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 26 publications
2
119
0
7
Order By: Relevance
“…Further research has supported the refinement proposed by Kim (2006) that could be implemented in PARSCALE. Several studies have investigated the ability of this method to capture the differences in the ability distributions of the nonequivalent groups and found that the refinement did correct for the bias in many circumstances (e.g., Baldwin et al, 2007;.…”
Section: Research On Fcip Equatingmentioning
confidence: 76%
See 2 more Smart Citations
“…Further research has supported the refinement proposed by Kim (2006) that could be implemented in PARSCALE. Several studies have investigated the ability of this method to capture the differences in the ability distributions of the nonequivalent groups and found that the refinement did correct for the bias in many circumstances (e.g., Baldwin et al, 2007;.…”
Section: Research On Fcip Equatingmentioning
confidence: 76%
“…It was necessary to consider the performance of the FCIP methods when used over multiple years and under more realistic contexts. To differentiate the methods of implementing FCIP, FCIP-1 will refer to the typical way that FCIP is performed, and FCIP-2 will refer to the adjustment suggested by Kim (2006), which, in his study, led to improvements in the estimation of proficiency estimation when growth was present from one test administration to the next.…”
Section: Scaling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Item response theory (IRT) is a psychometric model which is based on the idea that the probability of a correct response to an item is a mathematical function of person and item parameters (Kim, 2006). IRT provides a basis for estimating the parameters, determine how well the data conformed to the model and investigate how to measure the psychometric properties.…”
Section: Item Response Theory (Irt)mentioning
confidence: 99%
“…The sample size recommended in the literature varies between 50 and 1000 persons (e.g. Kim 2006, Linacre 1994, Tsutakawa & Johnson 1990. Because IRT has been a prevalent CAT approach for decades, it seems logical to apply IRT for adaptive item sequencing in learning environments that consist of simple items.…”
Section: Introductionmentioning
confidence: 99%